MicroRNA 628-5p as a Novel Biomarker for Cardiac Allograft Vasculopathy. Issue 1 (January 2017) - Neumann, Anneke; Napp, L. Christian; Kleeberger, Jan A.; Benecke, Nils; Pfanne, Angelika; Haverich, Axel; Thum, Thomas; Bara, Christoph
Abstract : Background: Cardiac allograft vasculopathy (CAV) remains the leading cause of morbidity and mortality after orthotopic heart transplantation (OHT). Because of its clinically silent progression and lack of symptoms, detection is often difficult and invasive coronary angiography is performed routinely. To date, there are no established noninvasive biomarkers available for prediction of CAV in transplanted patients. MicroRNAs (miRNAs) are highly conserved, small noncoding RNA molecules that negatively regulate gene expression. As they are detectable in peripheral blood, recent studies have suggested miRNAs as biomarkers for various cardiovascular diseases. Thus, we hypothesized that circulating miRNAs may serve as noninvasive biomarkers for CAV. Methods: To determine the regulation of circulating miRNAs, we performed miRNA profiling studies in plasma samples of OHT patients with confirmed high-degree CAV and a matched control group consisting of patients without any signs of CAV at least 5 years after OHT. Candidate miRNAs were verified by quantitative reverse transcriptase polymerase chain reaction. Results: Microarray analysis revealed 5 candidate miRNAs (miR-34a, miR-98, miR-155, miR-204, miR-628-5p) that were differentially regulated in plasma samples of patients with CAV and therefore were selected for verification by quantitative reverse transcriptase polymerase chain reaction. In CAV patients, plasma levels of miR-628-5p and miR-155 were significantly increased ( P = 0.001 and P = 0.028, respectively). A miR628-5p value above 1.336 was able to predict CAV with a sensitivity of 72% and a specificity of 83%. Conclusions: For the first time, the present study identifies the circulating miRNA miR-628-5p as a novel potential biomarker of CAV in patients after OHT. Abstract : In order to predict cardiac allograft vasculopathy (CAV) in heart transplant recipients, the authors test noninvasive biomarkers, circulating miRNAs, in patients with or without CAV. Out of 5 candidates, miR628-5p appears to be able to predict CAV with a 72% sensitivity and 83% specificity. Supplemental digital content is available in the text.